2015
DOI: 10.1038/jp.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and developmental speech/language disorders in late preterm, early term and term infants

Abstract: Late preterm and early term deliveries have adverse long-term neurodevelopmental outcomes, and these outcomes should be considered when determining the timing of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 19 publications
1
52
0
2
Order By: Relevance
“…Some studies assessed more than one outcome and are included in several tables. The studies were carried out in Europe, the USA, Australia, Canada, Hong Kong, Bangladesh and Japan . Thirty‐six studies were population‐based studies, three were national multicenter studies and three were single‐center studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies assessed more than one outcome and are included in several tables. The studies were carried out in Europe, the USA, Australia, Canada, Hong Kong, Bangladesh and Japan . Thirty‐six studies were population‐based studies, three were national multicenter studies and three were single‐center studies .…”
Section: Resultsmentioning
confidence: 99%
“…The studies were carried out in Europe, the USA, Australia, Canada, Hong Kong, Bangladesh and Japan . Thirty‐six studies were population‐based studies, three were national multicenter studies and three were single‐center studies . All the included studies were observational: 41 studies were cohort studies and one was a case‐control study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a multicenter, randomized trial demonstrated that administration of betamethasone to women at risk for late preterm delivery significantly reduced the risk of neonatal respiratory complications (8), bringing to the forefront the importance of this cohort and changes in practice management. Increased morbidity continues into childhood, with late preterm infants having a higher risk for respiratory disease notably asthma (9) and neurodevelopment delay and language disorders (10, 11). …”
Section: Introductionmentioning
confidence: 99%
“…Following the advances in perinatal care, an increasing number of preterm infants reach childhood (2). Negative effects of preterm birth on neurodevelopmental and psychiatric development of children and adolescents have been well documented (3)(4)(5)(6)(7)(8). Severe neurological impairment has been reported in 10 to 12% of school-aged children, who were born very preterm (less than 32 weeks of gestation) (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%